House Dust Mite Allergy Under Changing Environments - Acevedo, Nathalie (Allergy Asthma Immunol Res, 2019)
Environmental variations induced by industrialization and climate change partially explain the increase in prevalence and severity of allergic disease. One possible mechanism is the increase in allergen production leading to more exposure and sensitization in susceptible individuals. House dust mites (HDMs) are important sources of allergens inducing asthma and rhinitis, and experimentally they have been demonstrated to be very sensitive to microenvironment modifications; therefore, global or regional changes in temperature, humidity, air pollution or other environmental conditions could modify natural HDM growth, survival and allergen production. There is evidence that sensitization to HDMs has increased in some regions of the world, especially in the subtropical and tropical areas; however, the relationship of this increase with environmental changes is not so clear as has reported for pollen allergens. In this review, we address this point and explore the effects of current and predicted environmental changes on HDM growth, survival and allergen production, which could lead to immunoglobulin E (IgE) sensitization and allergic disease prevalence. We also assess the role of adjuvants of IgE responses, such as air pollution and helminth infections, and discuss the genetic and epigenetic aspects that could influence the adaptive process of humans to drastic and relatively recent environmental changes we are experiencing.